IZQUIERDO BRICHS, Ferran, ETHERINGTON, John y FELIU, Laura (eds.) (2017), Political Islam in a Time of Revolt, Palgrave Macmillan, Cham - Hernández-Justo, Tatiana (Revista de Estudios Internacionales Mediterráneos, 2017)
Revista de Estudios Internacionales Mediterráneos (REIM)